Legal Review of Consumer Protection in E-Commerce Tokopedia who Receive Goods not According to Order - Alrafly Bima Putra Wiratama (Proceeding International Conference Restructuring and Transforming Law, 2024)
E-commerce presents many challenges as it eliminates the opportunity for direct interaction and inspection between buyers and sellers. Buyers cannot physically inspect the product and must rely solely on the photos provided by the seller. In addition, not all sellers can be trusted to be honest in their transactions, leading to discrepancies between the information received and the actual product received. Defective goods are also often found in online marketplaces. Therefore, it is important for the government to make maximum efforts in providing legal protection for customers to prevent any sense of fraud in online transactions. The research approach uses empirical jurisprudence which is studied through qualitative descriptive analysis. The research findings show that there is already a solid legal framework regarding consumer protection in the field of e-commerce, as stipulated in Law Number 8 of 1999 concerning Consumer Protection and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. However, the responsibility of sellers on the Tokopedia e-commerce platform to compensate consumers for losses incurred during online transactions is not in line with existing laws. This is attributable to the fact that a considerable number of businesses are indifferent to consumer grievances and are reluctant to offer redress, despite unfavorable ratings from consumers and claims for compensation from third parties. The Tokopedia website does not facilitate the resolution of consumer complaints.